Pengaruh Penerapan e-Kinerja dan Motivasi terhadap Peningkatan Kinerja Pegawai Melalui Disiplin Kerja pada Dinas Pekerjaan Umum dan Penataan Ruang (PUPR) Kabupaten Bireuen - Syakila, Maya; Endang, Syahriani (Singkite Journal, 2023)
Research related to the performance of Bireuen Regency PUPR Service employees aims to examine it based on the application of e-performance, work motivation and mediated by employee work discipline factors. Applying quantitative descriptive methods with an associative type between variables, with a statistical approach through path analysis. The research results show that (a) there is a causal relationship between the implementation of e-performance, motivation and work discipline. (b) the implementation of e-kinerja has a significant effect on work discipline by 7.9% but has no effect on performance. (c) work motivation has a significant influence on work discipline of 82.5%, and also has an influence on performance of 31.4%. (d) Work discipline factors have a very high influence on the performance of Bireuen Regency PUPR Service employees, namely 67%.